Private returns to education for wage-employees and the self-employed in Uganda - Susan Namirembe Kavuma; Oliver Morrissey; Richard Upward (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The paper investigates the differences in private marginal returns to education between wage-employees and the self-employed in Uganda, using the Mincerian framework with pooled regression models. We use a two-wave household panel to estimate homogenous and heterogeneous private returns to education for both worker types. The study finds similar marginal returns to an additional year of schooling for both worker types. Further, the study finds the returns to educational qualifications are convex for wage-employees and concave for the self-employed. With regard to heterogeneous returns to education, we employ quantile regression models and find returns to education decreasing with quantile for both worker types.
Keywords: J24; J31; 330; returns to education; quantile regression